Fatal association of COVID‐19 and acute type A aortic dissection. Issue 3 (22nd March 2022) - Irilouzadian, Rana; Salehi Omran, Hossein; Alirezaei, Toktam
Abstract: Type A aortic dissection is a catastrophic event that requires prompt diagnosis and intervention to save the patient. It seems that type A aortic dissection in COVID‐19 patients has increased severity, and even with immediate diagnosis, it has a high mortality. Abstract : Type A aortic dissection is a catastrophic event that requires prompt diagnosis and intervention to save the patient. It seems that type A aortic dissection in COVID‐19 patients has increased severity, and even with immediate diagnosis, it has a high mortality.